Analisis Aspek Emotional dan Spiritual Capital Terhadap Peningkatan Produktivitas Kerja Pengrajin Desa Wisata Keris - Silmi Hidayati; Zainiyatul Afifah (IPM2KPE, 2023)
This research aims to analyze aspects of the application of emotional and spiritual capital in increasing the work productivity of craftsmen. This research uses a qualitative descriptive approach method with observation, interviews and literature studies as data sources. The research method used is the Miles and Huberman method, TRUSTWORTHINESS is used to replace